Comparison of serum ischemia modified albumin levels between preeclamptic and healthy pregnant women - Dinç Zuhal; Çakar Erbil; Kumru Pınar; Erel Özcan; Neşelioğlu Salim; Cimsit Nilüfer; Boz Gizem (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective Our aims to compare level of serum ischemia modified albümin(IMA) between healthy and preeclamptic pregnancies and to evaluate the relationship of IMA with preeclampsia, preeclampsia severity and perinatal outcomes. Methods Our study is a prospective case-control study. A total of 134 pregnant women (66 preeclamptic and 68 healthy pregnant) between 18-45 years of age and between 24- 41 gestational weeks participated. Serum IMA levels were measured by the Albumin Cobalt Binding (ACB) test. Results The mean IMA values were found to be significantly higher in the preeclampsia group compared to the control group (p<0,001). Patients were divided into 3 groups; severe preeclampsia(n=29), non-severe preeclampsia(n=37) and healthy pregnant(n=68). Statistically significant difference was not found between severe preeclampsia and non-severe preeclampsia (p=0.505). The performance of IMA values in predicting the development of preeclampsia among all participants was evaluated with Receiver Operating Characteristic (ROC) analysis. According to the ROC analysis, the best cut-off value at which the maximum area under the curve (AUC) was obtained was found when IMA>0.98(AUC: 0.690 95% Confidence Interval (CI): 0.600-0.781 p<0.001). When IMA threshold value of >0.98 was taken to predict preeclampsia; the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated as 65.15%, 64.71%, 64.18%, and 65.67%, respectively. Conclusion IMA level may be a useful new marker in recognizing and predicting preeclampsia. However, despite the power of recognizing the disease, serum IMA levels do not give an idea about the severity of the disease. More comprehensive studies are needed in order to use IMA levels in the diagnosis of preeclampsia.